Relationship between Participation in Classes for Pregnant Women and Exclusive Breastfeeding in the Working Area of UPT Puskesmas Barong Tongkok - Lisma Heriyanti; Inda Corniati; Kurniati Dwi Utami (Formosa Journal of Science and Technology, 2023)
This study aims to determine the relationship between class participation for pregnant women and exclusive breastfeeding at UPT Puskesmas Barong Tongkok, West Kutai Regency, in 2022. This type of research is an analytic survey with a cross sectional approach. The population in this study were breastfeeding mothers who had babies aged 6-11 months in the working area of ​​the UPT Puskesmas Barong Tongkok, West Kutai Regency, East Kalimantan, totaling 43 people. Sampling in this study used a purposive sampling technique with a total sample of 43 respondents. Data collection was carried out by interviewing and using a questionnaire. The data analysis technique uses the chi square test to determine the relationship between variables. The results of the hypothesis test obtained a p-value of 0.027 (<0.05), so it can be concluded that there is a relationship between class participation for pregnant women and exclusive breastfeeding at UPT Puskesmas Barong Tongkok, West Kutai Regency.